ANALISIS PENGARUH FREE CASH FLOW, KEBIJAKAN HUTANG DAN PERTUMBUHAN LABA TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Listing di BEI Periode Tahun 2009-2012 ) - Fandy Farid Panca Aji (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aimed to examine the effect of free cash flow, debt policy, the profit growth of the dividend policy. The independent variables are the free cash flow, debt policy and profit growth. The dependent variable in this study was measured by dividend policy Dividend Payout Ratio. This type of research is explanative research. The population used in this research are manufacturing companies listed on the Stock Exchange during the period of 2009-2012. The sampling technique used in this study are saturated purposive sampling and obtained eight samples. This study used secondary data obtained from the annual report from the Indonesia Stock Exchange (BEI) in the period 2009-2012. The analytical methods used to analyze the data is multiple regression. Based on the results of testing this hypothesis, it is evident that (1) free cash flow does not affect the dividend policy. (2) debt policies affect the dividend policy. (3) income growth effect on dividend policy. Keywords: dividend policy, free cash flow, debt policy, profit growth.